Dietary chia seed induced changes in hepatic transcription factors and their target lipogenic and oxidative enzyme activities in dyslipidaemic insulin-resistant rats - Rossi, Andrea Silvana (2013)
The present study analyses the effect of dietary chia seed rich in n-3 a-linolenic acid on the mechanisms underlying dyslipidaemia and liver steatosis developed in rats fed a sucrose-rich diet (SRD) for either 3 weeks or 5 months. The key hepatic enzyme activities such as fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC), glucose-6-phosphate dehydrogenase (G-6-PDH), carnitine palmitoyltransferase-1 (CPT-1) and fatty acid oxidase (FAO) involved in lipid metabolism and the protein mass levels of sterol regulatory element-binding protein-1 (SREBP-1) and PPARa were studied. (1) For 3 weeks, Wistar rats were fed either a SRD with 11% of maize oil (MO) as dietary fat or a SRD in which chia seed replaced MO (SRD þ Chia). (2) A second group of rats were fed a SRD for 3 months. Afterwards, half the rats continued with the SRD while for the other half, MO was replaced by chia for 2 months (SRD þ Chia). In a control group, maize starch replaced sucrose. Liver TAG and the aforementioned parameters were analysed in all groups. The replacement of MO by chia in the SRD prevented (3 weeks) or improved/normalised (5 months) increases in dyslipidaemia, liver TAG, FAS, ACC and G-6-PDH activities, and increased FAO and CPT-1 activities. Protein levels of PPARa increased, and the increased mature form of SREBP-1 protein levels in the SRD was normalised by chia in both protocols (1 and 2). The present study provides new data regarding some key mechanisms related to the fate of hepatic fatty acid metabolism that seem to be involved in the effect of dietary chia seed in preventing and normalising/ improving dyslipidaemia and liver steatosis in an insulin-resistant rat model.